1994
DOI: 10.1172/jci117579
|View full text |Cite
|
Sign up to set email alerts
|

Increases of intracellular magnesium promote glycodeoxycholate-induced apoptosis in rat hepatocytes.

Abstract: Invest. 1994Invest. . 94:2183Invest. -2192

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
173
1
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 258 publications
(184 citation statements)
references
References 55 publications
9
173
1
1
Order By: Relevance
“…Mg 2 þ mobilization is an early event in Fas-mediated apoptosis in B cells 31 and in glycodeoxycholate-induced apoptosis in rat hepatocytes. 32 An increase in free cytosolic Mg 2 þ facilitates the BID-or Bax-mediated release of cytochrome c from the mitochondria. 31,33 Thus, binding of Mg 2 þ by Tf may contribute to the antiapoptotic effects of Tf.…”
Section: Discussionmentioning
confidence: 99%
“…Mg 2 þ mobilization is an early event in Fas-mediated apoptosis in B cells 31 and in glycodeoxycholate-induced apoptosis in rat hepatocytes. 32 An increase in free cytosolic Mg 2 þ facilitates the BID-or Bax-mediated release of cytochrome c from the mitochondria. 31,33 Thus, binding of Mg 2 þ by Tf may contribute to the antiapoptotic effects of Tf.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear changes indicative of apoptosis were quantitated using fluorescent microscopy and the nuclear fluorescent binding dye 4,6-diamidino-2-phenylindole (DAPI) as we have previously described in detail (37)(38)(39). Results were confirmed by confocal microscopy.…”
Section: Methodsmentioning
confidence: 99%
“…Results were confirmed by confocal microscopy. DNA was isolated from cultured cells and separated by agarose gel electrophoresis as we have also previously described in detail (18,38).…”
Section: Methodsmentioning
confidence: 99%
“…Membrane lipid peroxidation can induce damage, including transition in permeability and release of apoptotic factors that lead to cell death (Mattson 1998). Hydrophobic bile acids induce apoptosis in rat hepatocytes (Patel et al 1994). It is known that apoptotic changes occur in hepatocytes during primary biliary cirrhosis (Kuroki et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Patel et al (1994) reported that hydrophobic bile acids caused apoptosis of rat hepatocytes. It has been suggested that hepatotoxicity induced by hydrophobic bile acids is associated with cholestatic change (Strange et al 1979;Attili et al 1986;Hofmann 1990).…”
mentioning
confidence: 99%